THEOLOGY IN AN AGE OF CONTINGENCY - D.P. Veldsman (Acta Theologica)
A review of Hermans, C.A.M. & Schoeman, K. (eds). Series: International Practical Theology 21. (Zürich: LIT Verlag, 2019), 193 pp. ISBN 978-3-643-91108-7 (pb). €34.90. ISBN 978-3-643-96108-2 (pdf)